Application of Tithonia Compost as Alternative Synthetic Fertilizer Source N and K on Young Oil Palm Plantation - Enita, Enita; Hermansyah, Hermansyah; Prasetyo, Teguh Budi (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2020)
Currently, large oil palm plantations are cultivated on ultisol. Ultisol has various constraints in its utilization for the cultivation of plants, because it has high exchangeable Al, low pH, low soil organic nutrient contained, and soil nutrients such as N, P, K, Ca, Mg. Large quantities and continuous fertilizer are needed for a long time. To solve these problems required to look for alternative fertilizers. These alternative fertilizers are expected to reduce the use of synthetic fertilizers without decreasing production and are available forever. Efforts to produce that location organic matter are the right choice. Tithonia can be grown in the form of alley cropping at young palm plantations. A series of experiments have been conducted at Andalas University experimental farm in Padang, West Sumatra Province. This study used the Factorial design. The treatments are tithonia compost and Lime application. There are 3 rd compost doses in 3 replication each treatment. The experimental obtained that tithonia compost dosage 25% and 50% + 25% and 50% synthetic fertilizer were changed soil chemical properties such as increased 0.94 units soil pH, availability of nutrient contained; 6.22% C-organic, 0.25% N-total, 0.37me/100g exchangeable K, 2.74 me/100g exchangeable-Ca, 0.29 me/100g exchangeable-Mg, in the soil, as well as the decrease of exchangeable Al. Furthermore supporting plant growth such as (plant height, plant length, and the number of the leaf). Liming not significantly different for soil chemical properties and growth of oil palm. The higher the compost dose is given the better the growth of oil palms. Cultivation of tithonia as alley cropping at oil palm plantation can be used as composite materials for synthetic fertilizer substitute source N and K